Histological study in liver of albino mice post exposing to shisha smoke - Nada Abdulrahman F. Al-Easawi; Muhammad Nafea Ali Al-Azzawi (World Journal of Experimental Biosciences, 2015)
The effect of shisha smoking on liver parenchyma tissues were evaluated in (120) male adult mice. The animals were divided into four groups according to kind of exposed smoke (cigarette, shisha and mixture of cigarette and shisha). The mice exposed to fresh air considered as control group. A special inhalation chamber designed locally was used to expose the animals to different kinds of smokes. Exposure to cigarette smoke was done for 5 min/day, while exposure to shisha smoke was done for 15 min /day for 4, 8, 12 weeks. The tissues of control and exposed groups were processed for histological study. The results showed different histological changes such as hepatocytes degeneration, congestion, sinusoid dilation and infiltration of inflammatory cells in liver parenchyma tissues. These changes observed clearly when the period of exposure increased especially in groups exposed to shisha smoke and shisha plus cigarette smoke for 12 weeks. The results showed that shisha smoke causes mild damage in liver parenchyma tissue and this damage increased concomitantly with the increase of duration of exposure.
Keywords: Histological effects, Liver, Mice, Shisha smoke.